2010
DOI: 10.1073/pnas.1013603107
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic apurinic/apyrimidinic (AP) endonuclease activity enables Bacillus subtilis DNA polymerase X to recognize, incise, and further repair abasic sites

Abstract: The N-glycosidic bond can be hydrolyzed spontaneously or by glycosylases during removal of damaged bases by the base excision repair pathway, leading to the formation of highly mutagenic apurinic/apyrimidinic (AP) sites. Organisms encode for evolutionarily conserved repair machinery, including specific AP endonucleases that cleave the DNA backbone 5′ to the AP site to prime further DNA repair synthesis. We report on the DNA polymerase X from the bacterium Bacillus subtilis (PolX Bs ) that, along with polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 49 publications
6
37
0
Order By: Relevance
“…Polymerase activity is increased by the presence of a phosphate group on the 5= terminus 1 to 5 nucleotides downstream of a 3=-OH (14). In addition, it was shown that PolX is able to nick a DNA substrate containing a nucleotide analog that mimics an AP site (15). The combination of AP endonuclease activity and the preference of its polymerase activity for small gapped substrates strongly suggests that PolX may be the primary polymerase that repairs small lesions, such as those produced by BER.…”
Section: Processing Of Apurinic/apyrimidinic Sitesmentioning
confidence: 99%
See 3 more Smart Citations
“…Polymerase activity is increased by the presence of a phosphate group on the 5= terminus 1 to 5 nucleotides downstream of a 3=-OH (14). In addition, it was shown that PolX is able to nick a DNA substrate containing a nucleotide analog that mimics an AP site (15). The combination of AP endonuclease activity and the preference of its polymerase activity for small gapped substrates strongly suggests that PolX may be the primary polymerase that repairs small lesions, such as those produced by BER.…”
Section: Processing Of Apurinic/apyrimidinic Sitesmentioning
confidence: 99%
“…The combination of AP endonuclease activity and the preference of its polymerase activity for small gapped substrates strongly suggests that PolX may be the primary polymerase that repairs small lesions, such as those produced by BER. Furthermore, PolX possesses a 3=-5= exonuclease activity which was shown to process AP sites that were cleaved on the 3= side by an AP lyase (15). Lyase cleavage produces a 3=-phospho-␣,␤-unsaturated aldehyde (3=-PUA), a group that blocks replication unless it is processed further (15).…”
Section: Processing Of Apurinic/apyrimidinic Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…maintaining genomic stability combined with proper replication (Banos et al, 2010). Yet, particularly advantageous to the evolution of BER was the recruitment of a class of enzymes known as glycosylases that specifically undertake the task of finding and removing damaged bases as a form of preventive measure to ensure the ''health'' of a cells' genome (O'Brien, 2006).…”
Section: Rios and Tormentioning
confidence: 99%